The Strategic Management of the Madrasa Principal in Improving the Quality of Educational Services: A Case Study at MA Al Ittihad - Susanto, Mimbar; Imam Baihaqi; Lukman Riyadi; Sri Wahyuningsih; Abdul Hamid (The Future of Education Journal, 2026)
Improving the quality of educational services is a crucial demand in educational management, particularly within Islamic educational institutions under the supervision of the Ministry of Religious Affairs. The madrasa principal plays a strategic role as a policymaker and change agent in efforts to enhance educational quality sustainably. This study aims to analyze the planning, implementation, and control of the principal’s strategic programs in improving educational quality at MA Al Ittihad. The research employed a qualitative approach using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Data were collected through interviews with the madrasa principal and related stakeholders. The findings indicate that strategic planning was carried out through the formulation of the school’s vision, mission, and work programs oriented toward improving educational service quality. Strategy implementation was realized through strengthening teacher competencies, improving academic service systems, and optimizing educational facilities and infrastructure. Strategic program control was conducted through periodic evaluation and continuous supervision of program implementation. The SWOT analysis reveals that the success of improving educational quality is influenced by the principal’s ability to leverage internal strengths and external opportunities while minimizing weaknesses and threats. The study concludes that the principal’s strategic management plays a significant role in enhancing the quality of educational services at MA Al Ittihad.